The Effect of Sensor-Based Elasticity Learning Media to Improve Student Creativity - Susilawati Susilawati; Wahyudi Wahyudi; Desi Asriani (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study was to determine the effect of sensor-based elasticity learning media to increase students' creativity. This type of research uses quasi-experimental research with the type of research design in the form of a nonequivalent control group design. The population of this study was all class XI MIPA of Praya 2 Public High School. The research sample consisted of class XI MIPA 1 with 29 students as the control class, and class XI MIPA 2 with 28 students as the experimental class. Sampling was carried out using the purposive sampling method. The instrument used to measure student creativity is a creativity test in the form of a description of 8 questions. The creativity test instrument used has been tested for validity, reliability test, level of difficulty test, and differential power test. The results of hypothesis testing based on pre-test and post-test value data are tcount greater than ttable with a value of 6.56 greater than 1.671 categorized as Ho being rejected and Ha being accepted. So it can be concluded that there is an influence of sensor-based elasticity learning media to increase student creativity